The Essence of Interactive Methods In The Development Of Students' Knowledge Of Technical Safety In The Credit-Module System - Abdurakhmonov Jahongir Sherali o’g’li (Academia One Publishing, 2024)
This article will talk about the essence of interactive methods in the development of students' knowledge of Technical Safety. The effectiveness of interactive methods and reliable aspects in their application are illustrated, the difference between an traditional, interactive lesson is studied and a conclusion is drawn
Keywords: Education; teacher; interactive; technical